The seeds of change [large type] - Snelling, Lauraine; Giron, Kiersti (Snelling, Lauraine. Leah's garden, 2021)
"Larkspur Nielsen is ready for a change. Her parents have passed on, and her older brother is successfully running the family business. She bristles at the small-mindedness that permeates life in her small Ohio community, and she sees little chance of a satisfying future there. She has a little money saved, and after turning the tables on a crooked gambler who had fleeced several locals, including her younger brother, she can stake a new start for herself and her three sisters. As the gambler's threats of revenge echo in her ears, she and her sisters head to Independence, Missouri, to join a wagon train bound for Oregon. Knowing that four women traveling together will draw unwanted attention, Larkspur dons a disguise, passing herself off as "Clark" Nielsen, accompanying his three sisters. But maintaining the ruse is more difficult than Larkspur imagined, as is protecting her headstrong, starry-eyed sisters from difficult circumstances and eligible young men. Will reaching their goal prove too much for them?"--